UPAH BURUH ONDERNEMING KARET DI ACEH TIMUR, 1907-1939 - Mawardi Umar (Humaniora, 2009)
This study aims at investigating the correlation between thewage level and the well being of the rubber plantation enterpriseworkers in East Aceh in the period of 1907 to 1939. It is of highsignificance in the historiography of Aceh because no studies onAceh have been found that examine plantation enterpriseworkers. The major source of this study is the annual reports ofthe Labor Inspectorate from 1907 to 1939, the collection ofNational Library, Jakarta.        The results of the study indicate that the wage of theplantation enterprise workers in East Aceh was very low andworth only for subsistence and determined unilaterally by theenterprise. The workers contributed nothing to the wagedetermination. The wage level was adjusted to the living cost,especially the price of rice, and the financial condition of theenterprise. Therefore, the living standard of the rubber plantationworkers in East Aceh never changed although their wageincreased.